MORAL EDUCATION DALAM MENGATASI EPICUROS HEDONISM PERSPEKTIF IMAM AL-GHAZALI - Abd Hamid Wahid; Alfirqotul Falah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
deterioration due to moral crisis resulted in many cases of adolescents which also involved students who were increasingly concerned with the many moral deviations such as drug problems, marital sexual relations, abortion, fights, fights and violence. This phenomenon makes what the world of education in Indonesia can not withstand moral degeneration that occurs as a result of education that is still more on cognitive problems. The method used in this research is descriptive qualitative, which is describing morals in the opinion of Imam al-Ghozali. In the opinion of Imam Alghozali giving a positive response to moral education becomes very important so that the main points and pressures can be found to be the basis and reference in the development of Islamic education as expected. One of the goals of Islamic education is to form a Muslim person who is close to perfection by internalizing moral education.